Культурология: Учеб. пособие для вузов / А. И. Кравченко - Кравченко А. И. (Gaudeamus, 2001)
Экземпляры: аб. (2002) / Инвентарный номер: 44020 / Цена: / Сис.шифр: 71.0 / Авт.знак: К 78 / ГРНТИ: 13.01 / ББК: 71.0я7